(untitled) (Biological Sciences - PJSIR, 1994)
Solution equilibria for some rare-earth metal ions with valine have been studied potentiometrically in aqueous medium at temperatures from 25 to 55"and ionic strengths (l) from 0.1 to 1.0mol dm? NaCl04 • The thermodynamic parameters H , S and G for the formation processes were evaluated in terms of temperature, ionic strength and nature of metal ion present. The stability of the complexes was found to be: La(III) <Nd(III) <Gd(lII) <Eu(lII) <Yb(III) < Lu (III).